The Role of Work Environment and Work Motivation in Increasing Employee Performance - suwarsito suwarsito (Universitas Bina Sarana Informatika, 2020)
This study aims to explain the influence of environment of work variables and motivation of work on the performance of Wahana Visi Indonesia (WVI) employees. The methods of data collection in this study used a survey method through a questionnaire. The results of this study show that the work environment significantly influences the work motivation of WVI's employees. These results are shown from the significance value of the t test = 0.000 smaller than α = 0.05 with the regression coefficient = 3.69. The work environment significantly influences the performance of WVI's employees as shown by the significance value of the t test = 0.000 less than α = 0.05. Work environment and work motivation simultaneously have a significant effect on the performance of WVI's employees, as indicated by the significance value of the F = 0,000 test smaller than α = 0.05 and being able to affect to the performance variable of 0.585 or 58.5%. The remaining 41.5% is influenced by other variables not analyzed in this study.